CHRONIC EFFECT OF HYDROGYM IN PEOPLE WITH OBESITY AND CNCD POST-COVID: A PILOT STUDY (Arquivos do Mudi, 2023)
The objective of this study is to verify the effec of the practice of Hydrogymnastics as aregulatory factor for the treatment of obesity and post-COVID CNCDs. This is a descriptiveresearch with a comparative approach, carried out with individuals with obesity. A 16-weekIntervention program was applied, in which 40 volunteers participated, who were assigned toan Intervention Group (IG) and a Comparison Group (CG). The analysis was descriptivebetween pre and post test (GI= 26 and GC=14). Normality was contrasted for the totalsample, and by group (G1 and G2) for each of the measured variables. In the interventiongroup, some variables were maintained and did not change significantly, there wereimprovements only in DBP and HR. In the CG there were improvements only in the HRvariable, they also obtained improvements in weight, BMI, DBP and SBP, with a small effectsize. The Hydrogymnastic Training Program, performed in adults with obesity, in this studyshowed an improvement in the response of the double product: heart rate and systolic bloodpressure.